INTERNAL AND EXTERNAL FACTOR INFLUENCE ICT ADOPTION: A CASE of INDONESIAN SMEs - Lucy Chairoel; Tri Rachmat Riski (Jurnal Manajemen dan Kewirausahaan, 2018)
The using of Information Communication Technology (ICT) in the industry is growing fast. Nevertheless, Small Medium Enterprises (SMEs) in Indonesia do not follow these conditions. The influencing factor of ICT adoption has been identified as internal and external factors. Accordingly, the objective of the study is to identify the influence factor of using ICT adoption in Indonesian SMEs. The conceptual model in this study was the combination between Diffusion of Innovation (DOI) theory and The Technology-Organization-Environment (TEO) theory. The survey method for 146 SMEs selected conveniently in Indonesia. The distribution of data by online and data obtained is analysed using SEM/Smart-PLS program. The study has exogenous variable including technology, organization, managerial characteristic, and environment. The endogen variable is ICT adoption. The research found that ICT used was predicted by characteristic of management, organizational and technology.